منصة أجيال للتدريس الخصوصي الالكتروني - العشي, بهاء; العملة, معاذ; أبونجمة, نافذ (جامعة بوليتكنك فلسطين - نظم معلومات, 2021)
عد التعليم اإللكتروني من أهم أنماط التعليم في الوقت الحاضر، فالتكنولوجيا لغة العصر، وتكنولوجيا التعليم ً قد تمر الشعوب بفت ارت تتعطل فيها أصبحت من الضروريات األساسية لتطوير النظم التربوية والتعليمية. وأحيانا مرافق الحياة. لهذا وذاك استوحينا فكرة عمل منصة إلكترونية تعليمية، خصصنا هذه المنصة إلعطاء الدروس الخصوصية، في مجال مواد المنهاج الفلسطيني، للمراحل التعليمية من الصف األول وحتى التوجيهي. هذه المنصة تجمع المعلمين ذوي الكفاء والخبرة في المنهاج الفلسطيني، اللذين على استعداد إل عطاء دروس إلكترونية في هذه المواد، مع الطالب ال ارغبين بأخذ دروس في مواد المنهاج الفلسطيني، بحيث يقومون باالشت ارك في المنصة، ثم يختار الطالب من المواد التي يريدها، مع اختيار موعد من المواعيد التي يضعها المعلم. وكل هذا الحجز أو عقد اللقاءات ً يتم بشكٍل . E-learning is one of the most important forms of education at the present time, because technology is the language of the age, and educational technology has become one of the basic necessities for the development of educational systems. Sometimes people may go through periods in which life facilities are disrupted. For this and that, we were inspired by the idea of creating an educational electronic platform. We dedicated this platform to give private lessons, in the field of Palestinian curriculum materials, for the educational stages from the first grade to tawjihi. This platform brings together qualified and experienced teachers in the Palestinian curriculum, who are willing to give electronic lessons in these subjects, with students who wish to take lessons in the subjects of the Palestinian curriculum, so that they sign up in the platform, then the students choose from the subjects they want, with an appointment from the Appointments set by the teacher. And all this is done electronically, whether booking or holding meetings
no of pages 95 , نظم معلومات 2021
Keywords: التعليم الالكتروني